Genetically engineered Chlamydomonas reinhardtii as a photosynthetic solid-state cell factory to improve photobiotransformation of cyclohexanone to ε-caprolactone - Siivola, Tiia (My University, 2023)
With an acute environmental crisis at hand, sustainable production processes are more crucial than ever. Photosynthetic solid-state cell factories offer a promising solution because photosynthetic microorganisms can take up atmospheric CO2 by utilizing solar energy and be engineered to produce high-value compounds. One potential cell factory application is photobiotransformation, where a substrate is converted into a product using photosynthetically produced cofactors and oxygen. Immobilization of the cells to a solid state enables a high cell density and light-to-product conversion. In this study, a green alga Chlamydomonas reinhardtii expressing a heterologous cyclohexanone monooxygenase (CHMO) was used to produce ε-caprolactone, a precursor of the biodegradable plastic polycaprolactone, from a fed substrate cyclohexanone via photobiotransformation. Three thin-layer hydrogel matrices, in which the strain was immobilized, were compared: i) Ca2+-alginate, ii) Ca2+-polyvinyl alcohol (PVA)-TEMPO-oxidized cellulose nanofibers (TCNF), and iii) photocrosslinked, 3D bioprinted galactoglucomannan methacrylates (GGMMAs) with alginate. CHMO expression was studied using Western blotting to find the optimal time point for cell immobilization. ε-caprolactone formation was analyzed with gas chromatography and the production rate and duration between solid-state cells and a suspension were compared. Long-term, semi-continuous production was tested with TCNF hydrogels by performing photobiotransformations daily. The most suitable time point for cell immobilization was after three days of cell growth, which was a compromise between optimal CHMO expression and chlorophyll content. The photobiotransformation completed fastest in suspension, however, the maximum rate was highest in TCNF hydrogels. Maximum specific production rates based on chlorophyll and dry cell weight were also highest in TCNF hydrogels. Long-term ε-caprolactone production was successful, though the reaction slowed down after a few photobiotransformation cycles. In conclusion, solid-state cell factories offer an efficient and prominent platform for whole-cell photobiotransformation.
Keywords: cell factory, cell immobilization, Chlamydomonas reinhardtii, CHMO, ε-caprolactone, photobiotransformation, photosynthesis